Improving Students' Creativity with Creative Problem-Based Learning Models - M. Nazali Romadhon Hafild; Frianka Ivana Damayanti; Andi Aryandi (Journal of Adaptive Education, 2025)
This study aims to develop and implement Creative Problem Solving (CPS)-based Student Worksheets (LKPD) to improve students' creative thinking skills on fractions in fifth grade at SDN 1 Langkapura. In the context of the Independent Curriculum, teachers have the freedom to design innovative and contextual learning. However, the use of LKPD or interactive media has not been widely implemented in several schools in Bandar Lampung. This study is based on the view that concrete and interactive learning media can improve student creativity more effectively than conventional methods. Data from the Ministry of Education and Culture's School Education Report Card shows a decline in literacy and numeracy skills of students at SDN 1 Langkapura in the last three years. The implementation of CPS is expected to address this problem by providing more meaningful and problem-solving-based learning. Analysis of previous research results shows that the CPS learning model can improve students' learning outcomes and creative thinking skills. This study uses an experimental approach by comparing learning outcomes between the experimental class using CPS-based LKPD and the control class using conventional learning methods. The research method used is the ADDIE model development research. The research results are expected to contribute to improving the quality of learning in elementary schools and inspire the application of the CPS method in various educational contexts.